The Importance Of Local Factors In Visual Identity Design - Tarlakazan, Elif; Tarlakazan, Burak Erhan (INTERNATIONAL JOURNAL OF HUMANITIES AND ART RESEARCH, 2024)
Today, cities have; historical, geographical, architectural, social-cultural values, etc. Some local features and differences create some advantages, which differentiate cities from each other in terms of awareness. This situation creates urban memory and recognition; It highlights the concept of visual identity and branding. In the branding process, local elements and geographically indicated products play an important role. In addition to the historical, cultural and natural beauties of the cities, local characteristics such as symbols, colors, inhabitants, products and tastes are the elements of differentiating cities from each other and gaining identity. Identity can be defined as a concept expressed by documents, cards, numbers or other identifiers that contain identifiable characteristics and information that indicate the uniqueness of a person or object. Urban identity can be expressed as the act-process-activities of creating a memory about the city we live in by giving a human meaning to the features and visual elements that distinguish one city from another. The aim of this study is to reveal the importance of local features in the process of creating the visual identities of cities and to examine the impact of these features. Descriptive analysis technique, one of the qualitative research techniques, was used in the study. In line with the information obtained, suggestions have been developed to increase awareness in terms of visual emphasis and design approach to local factors in the process of creating visual identities of cities.

Günümüzde kentlerin sahip oldukları; tarihi, coğrafi, mimari, sosyal-kültürel değerler vb. kimi yerel özellik ve farklılıklar, bir takım avantajlar yaratmakta ve bu da bilinirlilik açısından şehirleri birbirlerinden ayrışmaktadırlar. Kent hafızasının oluşturulmasında ve tanınırlık anlamında bu durum; görsel kimlik ve markalaşma kavramını ön plana çıkarmaktadır. Markalaşma sürecinde ise yerel unsurlar ile coğrafi işaretli ürünler önemli rol oynamaktadır. Kentlerin tarihi, kültürel ve doğal güzelliklerinin yanı sıra sembolleri, renkleri, yaşayanları, ürünleri, lezzetleri gibi yerel özellikleri de şehirlerin birbirlerinden ayrılma ve kimlik kazanma unsurlarıdır. Kimlik, bir kişinin veya nesnenin benzersizliğini gösteren, tanımlanabilir özelliklerini ve bilgilerini içeren belge, kart, numara veya diğer tanıtıcılarla ifade edilen bir kavram olarak tanımlanabilir. Kent kimliği de bir kenti diğerinden ayıran özellikleri ve görsel unsurlarını insani bir anlamlandırma ile yaşanılan şehre dair bir bellek oluşturulması eylemi-süreci-faaliyetleri şeklinde ifade edilebilir. Bu çalışmanın amacı kentlerin görsel kimliklerinin oluşturulması sürecinde yerel özelliklerinin önemini ortaya koymak ve bu özelliklerin etkisini incelemektir. Çalışmada nitel araştırma tekniklerinden betimsel analiz tekniği kullanılmıştır. Ortaya çıkan bilgiler doğrultusunda, kentlerin görsel kimlik oluşturma sürecinde yerel etkenlere yönelik görsel vurgulama ve tasarım yaklaşımı bakımından bilinci artıracak öneriler geliştirilmiştir.
Keywords: Görsel Sanatlar (Diğer); Visual Arts (Other); Tasarım; Marka; Kurumsal Kimlik; Kent Kimliği; Design; Brand; Institutional Identity; Local Identity; 8. Economic growth; 11. Sustainability; 15. Life on land; 12. Responsible consumption